2022
DOI: 10.1002/cncr.34330
|View full text |Cite
|
Sign up to set email alerts
|

Race, place, and socioeconomic status: A path toward lung cancer early detection

Abstract: Although progress has been made, the majority of patients with non–small cell lung cancer are diagnosed at an advanced stage, with disparities being observed by race/ethnicity and socioeconomic status. There is a critical need to understand and ameliorate these disparities and to advance lung cancer equity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Socioeconomic status (SES) is a combined social and economic measure of a person's education, income, occupation, living conditions, and access to opportunities and resources. SES has been recognized as a key determinant of all-cause mortality, influencing a person's health throughout their lifespan [23,[48][49][50][51]. Moreover, among all cancers, SES has a big impact on lung cancer and the observed disparity in incidence, treatment, and outcome (Table 1) [52].…”
Section: Association Of Social Factors In Lung Cancer Disparitymentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic status (SES) is a combined social and economic measure of a person's education, income, occupation, living conditions, and access to opportunities and resources. SES has been recognized as a key determinant of all-cause mortality, influencing a person's health throughout their lifespan [23,[48][49][50][51]. Moreover, among all cancers, SES has a big impact on lung cancer and the observed disparity in incidence, treatment, and outcome (Table 1) [52].…”
Section: Association Of Social Factors In Lung Cancer Disparitymentioning
confidence: 99%
“…Several studies have shown an association between better quality of life and higher SES among patients diagnosed at early-stage lung cancer (i.e., stage I/II) [54]. To measure the impact on health outcomes, SES can be assessed at various levels, such as personal, interpersonal, and societal levels [48,50,51,55]. AAs tend to have lower economic status than all other ethnic groups in the United States.…”
Section: Association Of Social Factors In Lung Cancer Disparitymentioning
confidence: 99%